Temperature distributions in pavement and bridge slabs heated by using vertical ground-source heat pump systems - Balbay, Asim; Esen, Mehmet (Univ Estadual Maringa, Pro-Reitoria Pesquisa Pos-Graduacao, 2013)
Temperature distribution which occurs in pavement and bridge slabs heated for de-icing and snow melting during cold periods is determined by using vertical ground-source heat pump (GSHP) systems with U-tube ground heat exchanger (GHE). The bridge and pavement models (slabs) for de-icing and snow melting were constructed. A three-dimensional finite element model (FEM) was developed to simulate temperature distribution of bridge slab (BS) and pavement slab (PS). The temperature distribution simulations of PS and BS were conducted numerically by computational fluid dynamics (CFD) program named 'Fluent'. Congruence between the simulations and experimental data was determined.
Distribuições de temperatura no pavimento e ponte lajes aquecidas usando um sistema vertical de bomba de calor derivado da terra
Keywords: de-icing and snow melting; ground-source heat pump; ground heat exchanger; borehole; finite element method